Extraction and structural study of hemicellulose B from Yorkshire fog (Holcus lanatus) : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Chemistry at Massey University - Lee, Kim Nyuk (Massey University, 1970)
1.1 : Hemicellulose The structural carbohydrates are mixtures of polysaccharides which together with lignin, constitute the cell wall. Usually they are divided into three fractions: pectic substances, hemicellulose and cellulose. 1 Pectins, widely distributed in land plants are characterised by a main chain of 1-4 linked galacturonic acid units. They may also contain rhamnose, galactose, xylose, arabinose and fucose in varying amounts. These sugars form part of the main chain in some pectins and branch chains in others. 2 Cellulose is generally present in the plant cell as aggregates of fibrils or partly crystalline bundles. They consist of parallel chains of ß 1-4 linked glucose residues, where the chains are in perfect alignment, the cellulose has a crystalline structure. The cellulose fibrils are generally embedded in other polysaccharide material, e.g. the hemicelluloses in the higher plants. 3 [FROM INTRODUCTION]
Keywords: Hemicellulose; Holcus lanatus